Economic uncertainty and climate change exposure - Danisman, Gamze Ozturk; Bilyay-Erdogan, Seda; Demir, Ender (Academic Press Ltd- Elsevier Science Ltd, 2025)
This paper explores how economic uncertainty affects firms' climate change exposure. We use an extensive sample from 24 countries from 2002 to 2021. Employing a novel measure of firm-level climate change exposure developed by Sautner et al. (2023b), we empirically demonstrate that prior to the Paris Agreement in 2015, economic uncertainty leads to a decrease in climate change disclosures. However, after the Paris Agreement, our findings reveal a positive association between economic uncertainty and climate change exposure. The positive disclosure effect is primarily driven by higher climate-related opportunities and regulatory exposures. Our findings are robust when we employ alternative definitions for economic uncertainty, alternative samples, additional firm-level and country-level control variables, and alternative methodologies. We find that institutional and foreign ownership positively moderates the association between economic uncertainty and climate change exposure after the Paris Agreement. Further analysis investigates the moderating impact of country-level environmental performance indicators. We present novel empirical evidence suggesting that firms operating in countries with less climate vulnerability, higher readiness, more stringent environmental policies, superior climate protection performance, and higher environmental litigation risk tend to have higher climate change exposure in uncertain times.
Keywords: Climate Change; Economic Uncertainty; Paris Agreement; Ownership